25-Hydroxycholecalciferol Improves Cardiac Metabolic Adaption, Mitochondrial Biogenetics, and Redox Status to Ameliorate Pathological Remodeling and Functional Failure in Obese Chickens - Chiang, Shih-Kai; Sin, Mei-Ying; Lin, Jun-Wen; Siregar, Maraddin; Valdez, Gilmour; Chen, Yu-Hui; Chung, Thau Kiong; Walzem, Rosemary L.; Chang, Lin-Chu; Chen, Shuen-Ei (Antioxidants, 2024)
Broiler breeder hens allowed ad libitum (Ad) feed intake developed obesity and cardiac pathogenesis and thereby were susceptible to sudden death. A supplement of 69 µg 25-hydroxycholecalciferol (25-OH-D3)/kg feed rescued the livability of feed-restricted (R) and Ad-hens (mortality; 6.7% vs. 8.9% and 31.1% vs. 48.9%). Necropsy with the surviving counterparts along the time course confirmed alleviation of myocardial remodeling and functional failure by 25-OH-D3, as shown by BNP and MHC-β expressions, pathological hypertrophy, and cardiorespiratory responses (p < 0.05). 25-OH-D3 mitigated cardiac deficient bioenergetics in Ad-hens by rescuing PGC-1α activation, mitochondrial biogenesis, dynamics, and electron transport chain complex activities, and metabolic adaptions in glucose oxidation, pyruvate/lactate interconversion, TCA cycle, and β-oxidation, as well as in TG and ceramide accumulation to limit lipotoxic development (p < 0.05). Supplemental 25-OH-D3 also sustained Nrf2 activation and relieved MDA accumulation, protein carbonylation, and GSH depletion to potentiate cell survival in the failing heart (p < 0.05). Parts of the redox amendments were mediated via lessened blood hematocrit and heme metabolism, and improved iron status and related gene regulations (p < 0.05). In conclusion, 25-OH-D3 ameliorates cardiac pathological remodeling and functional compromise to rescue the livability of obese hens through metabolic flexibility and mitochondrial bioenergetics, and by operating at antioxidant defense, and heme and iron metabolism, to maintain redox homeostasis and sustain cell viability.